Effects of burning and weed control on vegetation cover and soil organic matter compartments in the Brazilian Amazon - Fabrício Marinho Lisbôa (Acta Agronómica)
The aim of this study was to evaluate the effects of burning and manual control of invasive species on a Latossolo Vermelho-Amarelo soil covered with Urochloa brizantha. Five soil samples were collected for pasture and forest, at 0-5 cm depth, to determine the accumulated respiration, microbial biomass carbon (MBC), mild organic matter, total organic carbon (TOC), water soluble carbon and MBC:TOC ratio. Three groups according soil grass coverage were selected: (1) group I with 33.5% of bare soil, (2) group 2 with 90% coverage and (3) group 3 with 53.4% coverage of invasive species. The highest value of TOC was found in forest (36.52 g/kg). The highest accumulative value of respiration in the soil was observed in group 3 (2.6 mg kg-1) and the highest MBC:TOC ratio was found in forest and group 3 (0.0138 and 0.0156, respectively). The highest water soluble carbon value was observed in the forest (21.08 mg/kg). No significant differences were found in MBC and mild organic matter. The high coverage percentage of U. brizantha favours high values of TOC and water soluble carbon. The greater diversity of species in grass covered soil favoured greater amount of organic matter and increased microbial activity.